1982
DOI: 10.1055/s-2008-1059597
|View full text |Cite
|
Sign up to set email alerts
|

Use of ACTH Fragments in Children with Infantile Spasms

Abstract: Referring to the article of Pente/la et al in this issue of Neuropediatrics we report on experiences with ACTH therapy in infantile spasms. In addition we want to point out the reasons which led us to use ACTH fragments for therapeutic trials in children with infantile spasms.Adrenocorticotropic hormone (ACTH) has been a useful drug in the treatment of petit mal since 1950 (Klein and Livingstone 1950). The compound was successfully used in its natural form with 39 amino acids (ACTHI-39) and in its fragmented f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Earlier clinical studies have shown that shorter fragments (4-9) of ACTH, which failed to release adrenal steroids, were not efficacious for infantile spasms (Willig and Lagenstein, 1982;Pentella et al, 1982). Currently available information explains the apparent discrepancy: new information about the binding of ACTH fragments to melanocortin receptors shows that while the 4-10 fragment used here activates these receptors, the 4-9 fragment does not (Adan and Gispen, 1997;Gantz et al, 1993).…”
Section: Implications Of Steroid-independent Effects Of Acth For mentioning
confidence: 71%
“…Earlier clinical studies have shown that shorter fragments (4-9) of ACTH, which failed to release adrenal steroids, were not efficacious for infantile spasms (Willig and Lagenstein, 1982;Pentella et al, 1982). Currently available information explains the apparent discrepancy: new information about the binding of ACTH fragments to melanocortin receptors shows that while the 4-10 fragment used here activates these receptors, the 4-9 fragment does not (Adan and Gispen, 1997;Gantz et al, 1993).…”
Section: Implications Of Steroid-independent Effects Of Acth For mentioning
confidence: 71%
“…There is much anecdotal evidence but little scientific basis for the use of ACTH or corticosteroids; a recent report has valiantly attempted to explain and rationalise the multiple aetiologies, efficacy of hormonal treatment, and even spontaneous resolution of infantile spasms.40 In addition there is considerable variation in the preparation, dose, and duration of treatment and relapses are common, whether on or off treatment. 26 [41][42][43][44][45] More importantly these drugs are associated with frequent, severe, and potentially fatal side effects. Drug related mortality may be as high as 5%.46 ACTH and corticosteroids have also not been shown conclusively to improve the long term outcome of either the development of chronic epilepsy (which occurs in over 65% of children) or mental retardation.…”
Section: Treatmentmentioning
confidence: 99%
“…It is interesting that, at all neurotransmitter receptors for which ACTHI-,, and ACTH1-24 have shown activity, the nonsteroidal fragments ACTHk9 or ACTHk,, (Schwyzer, 1980) have been less active. This may be clinically relevant since ACTHI-39, ACTHI-24, and ACTH,,, are effective against infantile spasms (Singer et al, 1980), whereas ACTHk9 and ACTHk,, are not (Willig and Lagenstein, 1982;Pentella et al, 1982). Only the long fragments potently increase cyclic-AMP, stimulate phosphoinositide hydrolysis and inhibit protein kinase phosphorylation, enhance lipid fluidity of synaptic plasma membranes, and stimulate protein synthesis (Jolles et al, 1980;Van Dongen et al, 1985).…”
Section: Discussionmentioning
confidence: 99%